Loss of function of PGAP1 as a cause of severe encephalopathy identified by Whole Exome Sequencing: Lessons of the bioinformatics pipeline. Issue 5 (October 2015) - Granzow, M.; Paramasivam, N.; Hinderhofer, K.; Fischer, C.; Chotewutmontri, S.; Kaufmann, L.; Evers, C.; Kotzaeridou, U.; Rohrschneider, K.; Schlesner, M.; Sturm, M.; Pinkert, S.; et al.
Abstract: We evaluated a multiple consanguineous Turkish family with two children, a boy and a girl, affected by severe encephalopathy, hypotonia, microcephaly and retinal dystrophy by a combination of linkage analysis and Whole Exome Sequencing (WES). We analyzed the sequence data by two different bioinformatics pipelines which did not differ in overall processing strategy but involved differences in software used, minor allele frequency (MAF) thresholds and reference data sets, the usage of in-house control exomes and filter settings to prioritize called variants. Assuming autosomal recessive mode of inheritance, only homozygous variants present in both children were considered. The resulting variant lists differed partially (nine variants identified by both pipelines, ten variants by only one pipeline). Major reasons for this discrepancy were different filters for MAF and different variant prioritizations. Combining the variant lists with the results of linkage analysis and further prioritization by expression data and prediction tools, an intronic homozygous splice variant (c.1090-2A>G; IVS9-2A>G; p.?) in PGAP1 (Post-GPI Attachment To Proteins 1) was identified and validated by cDNA analysis. PGAP1 ensures the first step of maturation of GPI (glycosylphosphatidylinositol)-anchor proteins. Recently, a homozygous loss-of-function mutation in PGAP1 has been reported in one family with two children affected by a similar phenotype. The present report not only illustrates the possible influence of specific filtering settings on the results of WES but also confirms PGAP1 as a cause of severe encephalopathy. Highlights: Results from two different bioinformatics pipelines analyzing WES data are compared. We identified a homozygous intronic splice site variant in the GPI-anchor gene PGAP1 . PGAP1 is confirmed as a cause of severe encephalopathy.